THE ROLE AND OPPORTUNITIES OF FOREIGN EXPERIENCE IN ORGANIZING EXTRA-CURRICULAR EDUCATIONAL ACTIVITIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the role of extracurricular activities in the personal, social and professional development of students based on foreign experience. Practices in higher education institutions in the USA, Finland, Germany, Japan and South Korea were compared. The results of the study showed that extracurricular activities effectively contribute to the development of students' soft skills, creativity and professional readiness. These experiences are also important as an important methodological direction for the education system of Uzbekistan.